GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 863 species occurrences available in GBIF matching the query: TaxonKey: Stomias atriventer Garman, 1899. The dataset includes 863 records from 24 constituent datasets: 636 records from LACM Vertebrate Collection. 1 records from NRM-Fishes. 5 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 6 records from Field Museum of Natural History (Zoology) Fish Collection. 1 records from Tulane University Museum of Natural History. 3 records from CNPE/Coleccion Nacional de Peces. 8 records from Museum Victoria provider for OZCAM. 6 records from Colección Nacional de Peces del IBUNAM. 5 records from The Fish Collection. 3 records from Fish Collection of Hokkaido University. 22 records from CAS Ichthyology (ICH). 6 records from Museum of Comparative Zoology, Harvard University. 100 records from Fishbase. 36 records from NMNH occurrence DwC-A. 1 records from Natural History Museum (London) Collection Specimens. 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 3 records from Geographically tagged INSDC sequences. 5 records from UWFC Ichthyology Collection. 1 records from UAM Fish Collection (Arctos). 1 records from CUMV Fish Collection (Arctos). 3 records from Australian Museum provider for OZCAM. 1 records from KUBI Ichthyology Collection. 4 records from UF FLMNH Ichthyology. 5 records from SBMNH Vertebrate Zoology.
Keywords: GBIF; biodiversity; species occurrences